Analysis of the Nutritional Content, Fiber Fractions, and Methane Emissions of Lemongrass Waste Feed Produced Through Fermentation Using White Rot Fungi - Abdan Dairon; Zidan Bayakku Win Ramadhan; Indra Wahyudi; Sitti Wajizah; Samadi Samadi (ANIMAL PRODUCTION, 2026)
This study was conducted to examine the effectiveness of Trametes versicolor, Phanerochaete chrysosporium, Lentinula edodes, and a consortium (Trametes versicolor + Phanerochaete chrysosporium) in enhancing the nutrient content and reducing the fiber fraction of fermented lemongrass waste. This study was conducted at the Faculty of Agriculture, Syiah Kuala University. Using the completely randomized design (CRD) with 5 treatments and 4 replicates, this study examined dry matter, crude protein, crude fiber, crude fat, ash, NFE, ADF, NDF, cellulose, hemicellulose, lignin, and methane emissions. The data were analyzed using ANOVA, followed by Duncan’s multiple range test. This study concludes there is a numerical trend toward higher crude protein content in treatment P4 (Consortium; 5.51 ± 1.26) compared with the control (4.12 ± 0.32); however, the difference was not statistically significant (p = 0.06). However, in the fiber fraction analysis, the NDF content was lowest in the control group (59.68±0.34) compared to treatments P1, P2, P3, and P4. The control treatment exhibited the highest methane emission (7.1 × 10⁴ ppm), whereas the consortium treatment (P4) produced the lowest methane emission (2.96 × 10⁴ ppm). ANOVA revealed a significant effect of treatment on methane emissions (p = 0.009), and Duncan's multiple range test confirmed that the consortium treatment differed significantly from the control. The greatest reduction in the consortium treatment indicates a synergistic effect among the fungi in modifying the substrate, thereby more effectively suppressing methane formation.